Chairside diagnostics in periodontics - P L Ravishankar; D Mithra; Priyankar Chakraborty; Aravind Kumar (Wolters Kluwer Medknow Publications, 2017)
In the field of periodontology, the success of any treatment is based on the accuracy of the initial diagnosis. Traditional clinical measurements used for periodontal diagnosis are often of limited usefulness as they are indicators of previous periodontal disease rather than the present disease activity. Many of the biochemical, microbiological, gingival crevicular fluid, and salivary diagnostic tests are commercially available chairside tests Offers, that make the monitoring of periodontal disease activity more efficient. Chairside diagnostic kits offer rapid, reproducible mode of diagnosis and the results can be used for patient motivation as well. This review highlights various chairside diagnostic kits that facilitate diagnosis and improve prognosis.